Hormesis effect of 2,4-d choline salt on soybean biometric variables - Pinheiro, Guilherme H.R.; Marques, Ricardo F. [UNESP]; Araújo, Prissila P.S.; Martins, Dagoberto [UNESP]; Marchi, Sidnei R. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2021)
Auxin-based herbicides, such as 2,4-dichlorophenoxyacetic acid (2,4-D), are lethal to plants at higher doses, but can enhance plant growth at nontoxic concentrations. The stimulating effect of low doses of a substance considered toxic is known as hormesis. This study used dose-response curves to assess the hormesis effect of low doses of 2,4-D choline salt herbicide on soybean (Glycine max (L.) Merr.) biometric variables with distinct growth habits at different phenological stages. A completely randomized experimental design with seven replicates was used, and the treatments consisted of six fractions of the average dose indicated on the label of 2,4-D choline salt formulation: 0 (control), 0.068, 0.684, 6.84, 68.4 and 684 g ae ha-1 applied at the plant’s phenological stages second node with fully developed leaves (V2) or fifth node with fully developed leaves (V5). The plants were assessed for their main biometric parameters. The results were analyzed by ANOVA and, when significant, the hormesis model was tested. The maximum effect of hormesis on the main biometric parameters of soybean plants was estimated for doses between 0.20 and 36.01 g ae ha-1 of the herbicide and varies depending on the evaluated phenological stage of the plants. Low doses of 2,4-D choline salt herbicide may increase shoots, roots and total DM when applied at stages V2 and V5 of soybean with determinate growth habit and V2 of indeterminate growth habit. There was no adjustment of the hormesis model for the soybean plant with indeterminate growth habit at stage V5.
Keywords: 2; 4-Dichlorophenoxyacetic acid; Glycine max; Low doses; Morphology; Synthetic auxin